The Influence of Independence, Professional Ethics, and Competence on Auditor Performance with Organizational Commitment as a Mediating Variable - Nabil, Muhammad Fida Fadhlan; Muluk, M. Adrian (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The development of the public accounting profession has led to an increase in the number of businesses and various types of legal entities in the country. Public accountants play a vital role in the growth of modern business. Methods: This study aims to examine the impact of independence, professional ethics, and competence on auditor performance, with organizational commitment evaluated as a mediating variable. The study was carried out on auditors employed by KAP (Public Accounting Firms) in South Jakarta using a quantitative approach and the SEM-PLS analytical method.. Results: The findings indicate that the three independent variables exert a significant positive influence on auditor performance. However, organizational commitment was not found to significantly mediate the relationships between independence, professional ethics, competence, and auditor performance. These results reinforce attribution theory by underscoring the importance of both internal and external factors in enhancing auditor performance. Keywords: Independence, Professional Ethics, Competence, Organizational Commitment, Auditor Performance